ZIF-8 modified poly (m-phenylene isophthalamide) (PMIA) hybrid membrane for dye wastewater treatment. (5th November 2022) - Yang, Kailu; Liu, Xibo; Wang, Xinya; Hao, Tianxu; Zhang, Wei; Chen, Mingxing
The separation of dye/salt through the separation membranes is a great significance for the treatment of dye wastewater. In this study, a novel PMIA hybrid membrane was fabricated via nonsolvent induce phase separation (NIPS) method, in which porous zinc imidazolate framework-8 (ZIF-8) was utilized as a filler. The effect of ZIF-8 content on the structure and performance of PMIA/ZIF-8 membrane was investigated. The results showed that the structure and performance of the PMIA/ZIF-8 membrane could be controlled by changing the content of ZIF-8. The proper content of ZIF-8 was 0.45 wt% in this study. To further enhance the water flux of PMIA/ZIF-8 membrane, the concept of creating nanovoids within the ZIF-8 nanoparticle via wet-chemical etching method was explored in this study. The additional pore of ZIF-8 nanoparticles after wet-chemical etched endows PMIA/ZIF-8 membrane with additional pathways for water molecules. Hence, the PMIA/ZIF-8 membrane after wet-chemical etching showed higher separation performance for dye wastewater. The optimized PMIA/ZIF-8 membrane showed a water permeance of 104.7 L·m −2 ·h −1 and Congo red rejection of 98% at 0.1 MPa. The water permeance was about 1.5 times than that of the pristine PMIA/ZIF-8 membrane while the Congo red rejection was well maintained. Moreover, the PMIA/ZIF-8 membrane showed good thermal stability during the filtration process. These results indicated that PMIA/ZIF-8 membrane has potential application in dye wastewater treatment.